The accuracy of measuring velocity during weightlifting movements with five velocity-based training devices - Lemus, S. A.; Volz, M.; Blasdale, A.; Beron-Vera, F.; Chen, C.-B.; Mann, B. J.; Travascio, F. (International Journal of Sports Science & Coaching, 2024)
The use of weightlifting exercises is prevalent in competitive and recreational environments, as well as sport-specific training. Traditionally, weightlifting coaches prescribe specific training loads based on an individual's maximal ability. Velocity-based training offers an alternative method that promises to quantify strength based on velocity and provides information that increases competitiveness through real-time feedback. Various velocity measurement devices are available on the market. Their precision is critical for the adequate implementation of velocity-based training. The aim of the present study was to compare the concentric peak velocity measurements of five of these devices during two weightlifting movements, the snatch and clean, to data collected with a 12-camera motion capture system, which was considered as gold standard. It was hypothesized that the velocity measurement devices used in this study would vary in accuracy based on their retail prices. Velocity readings associated with light and moderate (40% and 70% of one-repetition max) loads were measured for both the snatch and clean performed by 12 competitive weightlifters. A least products regression was used to assess validity by comparing five devices against a criterion measure. A general linear model showed statistical differences in the velocities measured with these five devices (p < 0.001). Specifically, the GymAware RS linear position transducer was the most accurate device, demonstrating no fixed or proportional bias when used to quantify velocity during the snatch and clean. The remaining four devices significantly underestimated peak velocity, which would directly impact the daily planning of lifters` training. Practitioners must consider the error and bias of each device before implementing velocity-based training.